Dataset for pathology reporting of ductal carcinoma in situ, variants of lobular carcinoma in situ and low‐grade lesions: recommendations from the International Collaboration on Cancer Reporting (ICCR). Issue 4 (8th August 2022) - Fox, Stephen B; Webster, Fluer; Chen, Chih‐Jung; Chua, Boon; Collins, Laura; Foschini, Maaria‐Pia; Bruce Mann, G; Millar, Ewan; Pinder, Sarah E; Rakha, Emad; Shaaban, Abeer; Tan, Benjamin Y; et al.
Abstract : Aims: To describe a new international dataset for pathology reporting of ductal carcinoma in situ (DCIS), variants of lobular carcinoma in situ (LCIS) and low‐grade lesions (encapsulated papillary carcinoma, solid papillary carcinoma in situ, Paget's disease) produced by the International Collaboration on Cancer Reporting (ICCR). Methods and results: The ICCR, a global alliance of pathology bodies, uses a rigorous and efficient process for the development of evidence‐based, structured datasets for pathology reporting of common cancers. Their aim is to support quality pathology reporting and engender understanding between the breast surgeon, pathologist, and oncologist for optimal and uniform patient management globally. Here we describe the dataset for DCIS, some variants of LCIS (namely the pleomorphic and the florid variants), and low‐grade lesions by a multidisciplinary panel of internationally recognized experts. The agreed dataset comprises 12 core (required) and five noncore (recommended) elements suitable for both developed and low‐income jurisdictions, derived from a review of current evidence. Areas of contention were addressed using a pragmatic approach in the absence of evidence. Use of all core elements is the minimum reporting standard for any individual case. Commentary is provided, explaining each element's clinical relevance, definitions to be applied where appropriate for the agreed list of value options and the rationale for considering the element as core or noncore. Conclusion: This first internationally agreed dataset for DCIS, variants of LCIS, and low‐grade lesions reporting will enable their standardization of pathology reporting and enhance clinicopathological communication leading to improved patient outcomes. Widespread adoption will also facilitate international comparisons, multinational clinical trials, and help to improve the management of breast disease globally. Abstract :